2010
DOI: 10.1007/s10014-010-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

A case of atypical teratoid/rhabdoid tumor in an adult, with long survival

Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is a malignant tumor that mostly occurs in early childhood and has poor prognosis despite aggressive therapy. Adult cases are rare and, as far as we are aware, only 30 cases have been reported to date. Here we present the case of a 27-year-old female with left parietal AT/RT with the chief complaint of numbness of the right superior limb. First, the tumor was surgically removed and the diagnosis was grade II glioma. With additional radiotherapy, the clinical course afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
0
33
1
Order By: Relevance
“…[36] A recent report suggest that cerebral location of an AT/RT renders the tumor amenable to gross total resection as well as aggressive adjuvant chemoradiation therapy available in adults, which would not be tolerated by small children. [35] Therefore, immunohistochemical verification of this entity is very important for a proper treatment and better prognosis and AT/RT must be considered in the diagnosis of a high-grade tumor regardless of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] A recent report suggest that cerebral location of an AT/RT renders the tumor amenable to gross total resection as well as aggressive adjuvant chemoradiation therapy available in adults, which would not be tolerated by small children. [35] Therefore, immunohistochemical verification of this entity is very important for a proper treatment and better prognosis and AT/RT must be considered in the diagnosis of a high-grade tumor regardless of age.…”
Section: Discussionmentioning
confidence: 99%
“…[3238] Adult cases are rare and, as far as we are aware, only 42 cases have been reported to date [Table 1]. [2345910111213141516171821232425262729303133343536373941] Furthermore, there are only seven adult cases arising in the sellar turcica described in the literature. [224253034]…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Among the tumors in children below 1 year of age, AT/RT is now found nearly as frequently as CNS primitive neuroectodermal tumor/medulloblastoma. 7,18 Rarely, adults are diagnosed with AT/RT, which in this age group are mainly supratentorial, in contrast to young children, in whom infratentorial tumor location predominates. 18,19 In addition to the high cellularity of the tumor reflected by low signal on T2-weighted and ADC images, 20 bleeding residues, peripheral cysts, and a distinct pattern of contrast enhancement have been described as frequent findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,18 Rarely, adults are diagnosed with AT/RT, which in this age group are mainly supratentorial, in contrast to young children, in whom infratentorial tumor location predominates. 18,19 In addition to the high cellularity of the tumor reflected by low signal on T2-weighted and ADC images, 20 bleeding residues, peripheral cysts, and a distinct pattern of contrast enhancement have been described as frequent findings. [11][12][13]21 Rare reports of patients affected by AT/RT demonstrating involvement of the skull in children and adults exist.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, it was observed that AT/RT often demonstrates a loss of all or part of chromosome 22 [2,14]. But to our knowledge, AT/RTs have been reported in adults only in rare cases in the literature [11,13,[15][16][17], and only a few cases of AT/RTs have been investigated by comparative genomic hybridization (CGH) [4,18]. Studies have shown that the wide absence of recurrent genomic alterations other than SMARCB1 aberrations was recently confirmed in whole exome sequencing [9].…”
Section: Introductionmentioning
confidence: 92%